Extent of Adoption of Tomato Cultivation Practices among Farmers under Shade Nets in Kolar District of Karnataka - N Harisha,; Tulsiram, J; Meti, SK; Chandargi, DM; Joshi, Amrutha T (Indian Journal of Extension Education, 2021)
Indian agriculture is severely affected from climate change, fragmentation of cultivable land, water scarcity,  rapid urbanization, declining crop production and productivity, crash in market price, declining biodiversity, ever increasing population, increased demand for food especially vegetables. Protected cultivation has offered a new dimension to produce more in a limited area. The study was undertaken during the year 2016-17 in KolarÂ district. From each taluk respondents were selected by using purposive sampling procedure to constitute a sample size of 80 for the study. The study found that no one respondent raised nursery for seedlings. In caseÂ of cultural practices, with respect to ploughing, nearly two third partially adopted the recommended number of ploughings, no one adopted digging practice, whereas more than half of the respondents partially adopted theÂ recommended size of bed and nearly half of the respondents belonged to partial adoption category of bed treatment for tomato cultivation. Variables such as annual income, extension participation, exhibited positive and significant relationship with adoption behaviour of respondents.